Decomposition and discoloration of L-ascorbic acid freeze-dried with saccharides - Hung, Lan-hsin; Horagai, Yuka; Kimura, Yukitaka; Adachi, Shuji (Innovative food science & emerging technologies, 2007)
L-Ascorbic acid (vitamin C) was freeze-dried along with the following six types of wall materials: soluble soybean polysaccharide (SSPS), gum arabic (GA), maltodextrin (MD), α-cyclodextrin (α-CD), trehalose (Tre) and lactose (Lac). α-CD, Tre and Lac were used in mixtures with MD (weight ratio of 1:1). The decomposition kinetics of L-ascorbic acid in these powders stored at 80 °C and relative humidities of 11, 51 and 79% were expressed by the Weibull equation. The discoloration of the powders was also monitored by measuring the absorbance at 500 nm for solutions which were obtained by dissolving the systems in water. The L-ascorbic acid powders prepared with GA and SSPS were significantly discolored and the processes could be expressed by a modified Weibull equation. The discoloration of the L-ascorbic acid powders prepared with other saccharides was very slow. The discoloration rate constants were significantly greater at temperatures higher than the glass transition temperatures of the saccharides under the stated storage conditions, while the decomposition rate constant was only slightly affected by the system glass transition temperature. Decomposition and discoloration are examples of food deterioration. Food usually represents a multi-component system in which components interact with each other. Both their state and interaction would affect the deterioration. L-Ascorbic acid is one of the food components which are subject to decomposition and discoloration during storage. The decomposition and discoloration of L-ascorbic acid powders freeze-dried with saccharides were measured under various conditions and kinetically analyzed to understand an aspect of food deterioration.